Iraqi women’s movement, direction, its dimensions, her achievement - Chaloob, Banyas; Saleh, Thana (Al-Adab Journal, 2023)
This research aims to find out the impact of feminist protest on women’s economic demands for improvement. Its economic, social and political situation, as well as highlighting the feminist movement’s theme. Iraq and its importance in addressing the problems that women suffer from, and the feminist movement is meant as the movement that, it makes changes affect women by changing their status in society. As for ideology, it is thought, Feminism, which considers the patriarchal system a male or patriarchal system, is the cause of oppression of women throughout history, Therefore, this research seeks to answer the following questions: Did the women’s movement in Iraq after 2003 contribute to influencing economic and political reform? And social for women? What are the most important demands that the women’s movement focused on in Iraq? as well as Find out what are the intellectual trends of the feminist movement and their impact on achieving women’s demands?